Pembuatan Website UMKM Seblak Jontor Bajojo Menggunakkan Blogger Untuk Pengembangan Pemasaran Dan Promosi - Alya Fikriyyah Aqila; Rahmi Izzati Fitri; Maulana Malik Ibrahim (CV. ITTC INDONESIA, 2024)
Seblak Jontor Bajojo is a business that sells soft, chewy textured food with a very spicy taste located at Jl. Dr. Moh. Hatta No. 80, Anduring, West Sumatra, Padang city. Seblak with a preparation consisting of various seafood noodle crackers and vegetables that have been boiled or doused with hot water because of the chewy texture, seblak will taste more delicious when eaten while it is still hot. The author conducted interviews and documentation and created a website aimed at increasing the sales appeal of Seblak Jontor Bajojo. Apart from that, through the website the information that has been created is provided in detail, complete, and can provide a more attractive appearance. The method used in collecting data is a qualitative method by conducting interviews and documentation. The author made a visit and made direct observations to Seblak Jontor Bajojo to obtain the necessary data related to the design. This design produced a main media in the form of Seblak Jontor Bajojo Website Information Media